Methylation‐induced downregulation of TFPI‐2 causes TMPRSS4 overexpression and contributes to oncogenesis in a subset of non‐small‐cell lung carcinoma. Issue 1 (8th December 2014) - Hamamoto, Junko; Soejima, Kenzo; Naoki, Katsuhiko; Yasuda, Hiroyuki; Hayashi, Yuichiro; Yoda, Satoshi; Nakayama, Sohei; Satomi, Ryosuke; Terai, Hideki; Ikemura, Shinnosuke; Sato, Takashi; Arai, Daisuke; et al.
<x xml:space="preserve">Abstract</x> We identified transmembrane protease, serine 4 (TMPRSS4) as a putative, druggable target by screening surgically resected samples from 90 Japanese non‐small‐cell lung cancer (NSCLC) patients using cDNA microarray. TMPRSS4 has two druggable domains and was upregulated in 94.5% of the lung cancer specimens. Interestingly, we found that TMPRSS4 expression was associated with tissue factor pathway inhibitor 2 (TFPI‐2) expression in these clinical samples. In contrast to TMPRSS4, TFPI‐2 expression was downregulated in NSCLC samples. The in vitro induction of TFPI‐2 in lung cancer cell lines decreased the expression of TMPRSS4 mRNA levels. Reporter assay showed that TFPI‐2 inhibited transcription of TMPRSS4, although partially. Knockdown of TMPRSS4 reduced the proliferation rate in several lung cancer cell lines. When lung cancer cell lines were treated with 5‐aza‐2′‐deoxycytidine or trichostatin A, their proliferation rate and TMPRSS4 mRNA expression levels were also reduced through the upregulation of TFPI‐2 by decreasing its methylation in vitro. The TFPI‐2 methylation level in the low TMPRSS4 group appeared to be significantly low in NSCLC samples (P = 0.02). We found a novel molecular mechanism that TFPI‐2 negatively regulates cell growth by inhibiting transcription of TMPRSS4. We suggest that TMPRSS4 is upregulated by silencing of TFPI‐2 through aberrant DNA methylation and contributes to oncogenesis in NSCLC.